Corporate Social Responsibility (CSR) in Nepal: A Literature Review - Koirala, Narayan; Thapa, Asim (Innovative Research Journal, 2023)
Corporate sustainability is key for the success of corporate organizations including commercial banks. Investment in the social responsibility of the bank improves the reputation and ownership of the public towards the bank. This study has determined the relationship of corporate social responsibility (CSR) on the performance of commercial banks in Nepal. To bridge the gap, this study intends to clarify the basic tenets of CSR focusing on banking institutions as a center. Descriptive and archrival design is used in the article process to analyze the archive. Secondary data is used in the research. This research was based on corporate governance and its implications within commercial institutions of Nepal. This research examined previous literature.